THE PERFORMANCE OF TURBO CODED ORTHOGONAL FREQUENCY DIVISION MULTIPLEXING SYSTEM IN FADING CHANNEL - PRAMONO (NIM: 23206056), SUBUH
This research presents simulation results for the performance of turbo coded orthogonal frequency division multiplexing system, it is built with matlab 7.0 in fading channel condition rayleigh distributed. Channel coefficient is generated by jakes method. Iterative decoding caused iteratively exchange of extrinsic LLR between decoder one and decoder two until produced highly both polarization and reliability of soft decision. In addition to iterative decoding, size of block interleaver is the major factor to increased weight codeword and its distribution. Interleaver roles in declining of bit error floor slope. The results show that iterative decoding on turbo code needs three iterations at least to get optimum soft decision. The biggest interleaver's size (L : 4080 bits) produced the best turbo code’s bit error rate performance. In this system simulation, more subcarrier is used that produced better performance because of orthogonal frequency division multiplexing system. The last result shows that turbo code produced significantly coding gain to overcome doppler effect for mobile channel modelling.